The Effect of Video Blogging as Learning Media for Students’ Speaking Skills - Lumintang, Sheline Feranda; Aminin, Zainul (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to find out the extent of the effect of using video blogging for students’ speaking skills. This research bridges the gap between conventional language teaching practices and the preferences of today's learners who are accustomed to using multimedia content. This study used a pre-experimental method. Speaking tests are the research tool that will be administered to 36 students as a sample for this study. The results showed that the experimental class's average pre-test score was 57,3, and its average post-test score was 69,2. A Sig. (2-tailed) value of 0.000 was found in the independent sample t-test analysis findings, which is less than the predefined significance limit of 0.05. As a result, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. These findings indicate a significant effect of using video blogging as learning media for high school students' speaking skills.